Dental Erosion in Industry - Cate, H. J. Ten Bruggen (1968)
Five hundred and fifty-five acid workers were examined between March 1962 and October 1964. One hundred and seventy-six (31·7%) were affected by industrial dental erosion at the first examinations. In 33 cases (6·0%) the dentine was affected. During the period of the survey, 66 (20·4%) of 324 workers examined more than once showed evidence that erosion was progressing. The prevalence and incidence of erosion were highest among battery formation workers, lower among picklers, and least among other processes covered by the survey. The age of workers did not appear to influence their susceptibility to erosion. The habit of working with the lips slightly parted had little effect. Erosion superimposed upon attrition predisposed to more severe loss of tooth structure than either operating alone. Little inconvenience or functional disability was suffered by acid workers due to erosion. Twenty-seven (23·7%) of 114 erosions were considered to be disfiguring. Regular dental treatment was sought less by acid workers than by controls, and the oral hygiene of the latter was superior. There was no evidence to show any difference between caries experience among acid workers and controls. Calculus and periodontal disease were more prevalent among acid workers than among controls, but it was not possible to attribute this to the working environment. Black staining in iron picklers was considered to be due to the working environment. The use of closed acid containers or lip extraction on open acid vats prevented significant atmospheric contamination and diminished the prevalence of erosion. The use of wall fans and detergent foaming agents was helpful.